Dekonstruksi Makna Ya’juj dan Ma’juj dalam QS. al-Kahfi: 94: Analisis Ekoteologis melalui Hermeneutika Paul Ricoeur - Muhammad Fadli Rahman (UIN Sunan Kalijaga Yogyakarta, 2026)
Surah al-Kahf:94 recounts the story of a people who sought assistance from a king named Dhul-Qarnayn to construct a barrier. This wall was intended to separate them from Ya’juj and Ma’juj (Gog and Magog), who were known for spreading corruption and chaos across the land. As eras progress, so too does human knowledge and the necessity for guidance from the Holy Qur’an—the definitive manual for every Muslim.This article aims to present a contemporary interpretation of QS. al-Kahf:94 that resonates with modern readers, utilizing the hermeneutic framework proposed by Paul Ricoeur. The central research question is: How can QS. al-Kahf:94 be interpreted through the perspective of Paul Ricoeur’s hermeneutics? In the author’s view, Ya’juj and Ma’juj represent individuals or entities that commit systemic destruction on Earth. The devastation they cause involves the reckless destruction of the environment—treating nature as a mere commodity to be enjoyed and subsequently abandoned in a state of ruin without accountability. From this perspective, humanity views the natural world solely as an object for exploitation to achieve personal interests.In various exegetical literatures, interpretations of Ya’juj and Ma’juj vary significantly. Some scholars identify them as a specific tribe that will emerge to spread corruption before the Day of Judgment. Imran Hosein suggests that Ya’juj and Ma’juj refer to nuclear-armed nations intent on causing global destruction through warfare. Similarly, in his commentary, Buya Hamka defines Ya’juj and Ma’juj as any movement or force that brings about corruption and ruin on Earth QS. al-Kahfi:94 menceritakan kaum yang meminta pertolongan kepada seorang raja bernama Żulkarnain, agar membangunkan mereka sebuah tembok untuk memisahkan mereka dari Ya’juj dan Ma’juj yang suka merusak di bumi. Seiring dengan berkembangnya zaman maka berkembang pula ilmu pengetahuan dan kebutuhan manusia akan petunjuk dari kitab suci -al-Qur’an- yang menjadi pedoman bagi setiap muslim. Artikel ini bertujuan untuk menghadirkan pemaknaan QS. al-Kahfi:94 yang relate dengan pembaca, yang akan diteliti menggunakan hermeneutika yang digagas oleh Paul Ricoeur. Masalah yang dapat dirumuskan dari penelitian ini adalah, bagaimana pemaknaan QS.al-Kahfi:94 dalam perspektif hermenutika Paul Ricoeur? Ya’juj dan Ma’juj sendiri menurut hemat penulis merupakan manusia yang suka berbuat kerusakan di bumi, kerusakan yang mereka perbuat adalah menghancurkan alam secara serampangan, menjadikan alam hanya dinikmati kemudian ditinggal dalam keadaan rusak tanpa pertanggungjawaban, manusia menganggap alam sebagai sesuatu yang harus dieksploitasi demi meraih kepentingan pribadi. Dalam beberapa literatur tafsir, Ya’juj dan Ma’juj memiliki penafsiran yang beragam, ada yang mengatakan mereka adalah satu kaum yang suka berbuat kerusakan yang akan muncul sebelum hari kiamat. Imran Hosein yang menyebutkan Ya’juj dan Ma’juj merupakan bangsa-bangsa yang memiliki nuklir dan ingin melakukan kerusakan di muka bumi, dengan berperang. Begitu juga Buya Hamka dalam tafsirnya menyebut Ya’juj dan Ma’juj merupakan setiap gerak yang merusak di bumi.